Presidential Address: Sedimentology: A Tool for Mapping "Mill-Rock" - Lajoie, Jean (Geoscience Canada, 1977)
Abstract Mill-rock is a distinctive lithology composed of coarse volcaniclastics, observed close to many massive sulphide deposits of volcanogenic origin The general consensus ot opinion is that strata-bound base-metal sulphide deposits, associated with subaqueous volcanics, are located close to eruptive centres or vents. Volcaniclastics may be important guides to eruptive centres. The aim of the presentation is to review briefly what has been done, and to summarize the principles and techniques which we have used in mapping volcaniclastics. Gram size and bed thickness are the two properties most often used to establish vertical and lateral variations within the pile. These properties are generally compared within a single event or series of events such that the first mapping problem is one of correlation The principles are not different from those used in sedimentary rocks Authors working with grain size have used median, mean, and a representative of the coarsest fragments In our work we have found that the coarsest grain size gave better results It is a more reliable measurement of flow conditions and is easier to measure The hydrodynarnic behavior of pyroclastics should not be different from that of other mass-flow sediments, and by analogy, primary structure sequences, commonly present in volcaniclastics, may be used for paleogeographic reconstruction. Our work in the Noranda region shows that these sequences are a powerful tool, but that bed thickness is not a reliable paleogeographic indicator.